2016
DOI: 10.1002/bjs.10268
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of closure of the fascial defect during laparoscopic incisional and ventral hernia repair

Abstract: CFD during LIVHR reduces the rate of seroma formation and adverse hernia-site events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(74 citation statements)
references
References 50 publications
2
67
1
4
Order By: Relevance
“…to reduce the incidence of adverse hernia‐related events including recurrence, seroma formation, and mesh bulging . Several reports have indicated the effectiveness of IPOM‐Plus , and a recent systematic review concluded that IPOM‐Plus was more effective than sIPOM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to reduce the incidence of adverse hernia‐related events including recurrence, seroma formation, and mesh bulging . Several reports have indicated the effectiveness of IPOM‐Plus , and a recent systematic review concluded that IPOM‐Plus was more effective than sIPOM .…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic fascial defect closure with intraperitoneal onlay mesh reinforcement (IPOM-Plus) has been introduced to reduce adverse events in IHR (6), and satisfactory outcomes were reported in some studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). As compared with standard intraperitoneal onlay mesh without fascial closure (sIPOM), IPOM-Plus is expected to reduce the incidence of adverse hernia-site events (23). However, the literature did not mention the subgroups of hernia size and types of repair.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, nonrandomized studies tend to be more representative of patient populations routinely seen in clinical practice [38]. The approach of analysing non-randomized studies in a systematic manner through a meta-analysis is becoming increasingly prevalent nowadays as the resulting information can play an important role in informing practice and further investigation [39,40]. Another limitation of this review relates to the quality of the included studies, with none of the non-randomized studies meeting the minimal MINORS criteria [11] score of 16, and neither of the randomized trials reaching a Jadad score [12] of greater than 3.…”
Section: Discussionmentioning
confidence: 99%
“…Closure of the fascial defect was described in only four of the included studies, but its effect on recurrence is not fully clarified 4 . A meta-analysis 74 found an advantage of closing the hernia defect, but the results should be interpreted with care as the heterogeneity was 97 per cent.…”
Section: Discussionmentioning
confidence: 99%